Effect of abrasive water jet descaling process on surface quality of hot-rolled 304 stainless steel - Rui Guo; Cunlong Zhou; Zelin Chai; Chao Li; Zhengyi Jiang (Journal of Materials Research and Technology)
Based on a self-developed abrasive water jet (AWJ) descaling test bench, the effects of process parameters on surface roughness, plastic deformation, material erosion, and microhardness of hot-rolled 304 stainless steel were investigated. The results show that the AWJ descaling process changes the abrasive impact mode and the plastic deformation mechanism of the matrix by regulating the abrasive impact kinetic energy and the stress state of the matrix, thus determining the surface quality of the material. The jet pressure, jet distance and traverse speed regulate the surface quality through changing impact kinetic energy. The abrasive particle size affects the surface quality by altering both the micro-cutting mechanism and the impact kinetic energy. The jet angle controls material removal and plastic deformation by adjusting the ratio of normal and tangential stress to affect the surface quality. A gradient strengthening layer is formed on the surface of the AWJ descaling sample, which is positively correlated with the degree of plastic deformation. The strengthening mechanism is attributed to the combined effects of an increase in dislocation density, deformation-induced martensitic transformation and twin refinement. This study provides a theoretical basis and engineering guidance for the optimization of AWJ descaling process parameters.